2013
DOI: 10.7448/ias.16.1.18004
|View full text |Cite
|
Sign up to set email alerts
|

Virological outcome and patterns of HIV‐1 drug resistance in patients with 36 months’ antiretroviral therapy experience in Cameroon

Abstract: IntroductionThe current expansion of antiretroviral treatment (ART) in the developing world without routine virological monitoring still raises concerns on the outcome of the strategy in terms of virological success and drug resistance burden. We assessed the virological outcome and drug resistance mutations in patients with 36 months’ ART experience, and monitored according to the WHO public health approach in Cameroon.MethodsWe consecutively recruited between 2008 and 2009 patients attending a national refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
20
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 20 publications
17
20
1
Order By: Relevance
“…These findings are consistent with previous studies that have reported similar rates of acquired drug resistance mutations in Cameroon (8,23) and other African countries with similar ART programs (10,31,32). The most prevalent mutations identified were M184V and K103N.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are consistent with previous studies that have reported similar rates of acquired drug resistance mutations in Cameroon (8,23) and other African countries with similar ART programs (10,31,32). The most prevalent mutations identified were M184V and K103N.…”
Section: Discussionsupporting
confidence: 83%
“…Using the aforementioned criteria, M184V and T215Y/F were selected as nucleoside reverse transcriptase inhibitor (NRTI) resistance mutations, while K103N and Y181C were selected as non-NRTI (NNRTI). M184V is the most common (37% to 90%) of the NRTI resistance mutations causing high-level resistance to lamivudine (3TC) and (8,22,23). The drugs affected (FTC, 3TC, AZT, ABC, EFV, and NVP) are among those most commonly used in the regimens recommended by WHO guidelines for first-line treatment in resource-constrained countries, especially in sub-Saharan Africa (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been reported in Cameroon [22,23], in Republic of Central Africa [24] and in Republic of South Africa [25]. These observations show an importance to better manage patients undergoing ART by physicians for an earlier suppression of VL.…”
Section: Discussionsupporting
confidence: 77%
“…The therapy has dramatically decreased morbidity and mortality rates in patients with HIV-1 infection in both developed and less affluent countries [3,4]. However, incomplete viral suppression results in the spread of HIV-1 resistance to the drugs, which not only jeopardizes therapeutic effects for individuals, but also puts the entire global population at risk [5,6].…”
Section: Introductionmentioning
confidence: 99%